Retrospective Study: Characteristic of Herpes Zoster Patients - Ayuningati, Lia Kinasih; Indramaya, Diah Mira (Faculty Of Medicine Airlangga University, 2015)
Background: Herpes zoster (HZ) is a disease caused by the Varicella-zoster virus (VZV) that localized, primarily affects adults with characteristics of radicular pain, unilateral, and group of vesicles distributed according to dermatomes, innervated by a sensory nerve ganglion. Several risk factors for HZ is older populationand cellular immune dysfunction. Purpose: To evaluate general overview of HZ patients, hence better management can be provided. Methods: Retrospective study of newly diagnosed HZ patientsin Kemuning ward Dr. Soetomo General Hospital Surabaya during 2010-2013. Results: This study showed most commonly affected women (55.9%), themost common age was45-64 years old (40.7%)and the most common location was HZ thoracalis (31.4%). Conclusion: HZ is a common disease, which most commonly occured illness in elderlywith predisposing factors, that can determine the course of the disease, so we need proper management and education.Key words: herpes zoster, retrospective.